THEORETICAL AND METHODOLOGICAL BASIS OF TRAINING OF MANAGEMENT PERSONNEL IN THE PROCESS OF HIGHER PEDAGOGICAL EDUCATION - Khushnazarova Mamura Nodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the tasks set before the process of management personnel training in the reforms carried out in the process of higher pedagogical education, reforms aimed at raising the life of society to a new level of quality, the requirements set for the sphere of management of preschool education.